Quantitative analysis of ciliary ultrastructure in patients with primary ciliary dyskinesia - KARADAĞ, BÜLENT TANER; ERCAN, FERİHA; ŞİRVANCI, SERAP (ELSEVIER GMBH, 2008)
The present study was designed to investigate dynein arm and microtubule defects quantitatively in patients with respiratory disease and to establish the clinical relevance of dynein arm deficiency and microtubule abnormalities. Thirty-four patients with recurrent upper and/or lower respiratory infections were included in the study. Nasal mucosal brushings were fixed in glutaraldehyde and routine electron microscopic procedures were carried out. At least 20 cross-sectioned cilia were examined from each subject. Dynein arm and microtubular abnormalities were quantified and a statistical analysis was performed. Twenty-nine percent of the patients showed dynein arm deficiency and a further 21% had possible deficiency (PD). Microtubule defects in patients with dynein arm deficiency and PD were found to be significantly increased compared to the patients with no dynein arm deficiency. The most prominent defect in the dynein arm deficiency group was a translocation of central and/or peripheral microtubules. The high percentage of translocation defect in this group of patients suggests that these defects are primary, rather than secondary to infection. (C) 2007 Elsevier GmbH. All rights reserved.
Keywords: primary ciliary dyskinesia; cilia; ultrastructure; quantitative analysis; BRONCHIAL EPITHELIUM; ELECTRON-MICROSCOPY; CHILDREN; MICROTUBULES; DYSFUNCTION; BEAT